5 mm mini-incision laparoendoscopic single-site surgery of total hysterectomy: a report of five cases and literature review - J.L. Liu; J.M. Chen; Y.F. Zheng; X.W. Zhang; R.X. Shi (Clinical and Experimental Obstetrics & Gynecology)
Objective: To investigate the feasibility and safety of 5 mm mini-incision laparoendoscopic single-site surgery of total hysterectomy. Study design: A retrospective analysis was made to the clinical data of 5 patients who underwent 5 mm mini-incision single-site laparoscopic hysterectomy at the Department of Obstetrics and Gynecology, the Affiliated Changzhou No.2 People′s Hospital of Nanjing Medical University. Five patients were 40-52 years old between April 2018 and May 2018. Three of them diagnosed with cervical intraepithelial neoplasia grade III (CINIII); one of them diagnosed with endometrial atypical hyperplasia; One of them diagnosed with cervical cancer (Ia1 phase). Laparoscopic single-site hysterectomy was performed through a 5 mm mini-incision. Results: Five 5 mm mini-incision laparoendoscopic single-site operations were success and not changed to open abdomen operation. The mean operative time was (153 ± 34.02) minutes, in which the puncture establishes a part of the surgical path for 5-10 minutes, and the umbilical reconstruction part was 3-5 minutes; mean estimated blood loss was (60 ± 30.82) milliliters; The median temperature was 37.2 (36.5-37.5) ℃ on the first day after surgery; Postoperative anal exhaust time was 1.0-1.5 days and The length of hospital stay was 6-7 days. All the umbilical wounds healed well and the surgical scar was seen hardly after the operation. There were no umbilical hernia and other serious complications. Conclusion: 5 mm mini-incision laparoendoscopic single-site surgery of total hysterectomy may be safe and effective under the premise of mature laparoscopic technique.